Attack of the Clones… and the Issues of Clones - Lesko, Paul; Buckley, Kevin (Science and Technology Law Review, 2019)
Shortly after Advanced Cell Technology, Inc.’s announcement of their successful cloning of a human embryo, a worldwide uproar ensued culminating in both President Bush and the Vatican denouncing all types of human cloning. Since then, the national and international legislative landscape has changed dramatically. A number of foreign legislatures as well as the U.S. House of Representatives acted quickly attempting to outlaw human cloning and other aspects of human cloning. Now as the U.S. Senate begins debating these issues, it is important to engage in a detailed legal and economic analysis of the impact human cloning will have on the international community. Part I of this article is a hypothetical situation, which exemplifies some of the difficult situations that should be addressed by comprehensive human cloning legislation. Part II examines the processes of reproductive and therapeutic human cloning as well as their future markets. Part III discusses the current international and national legislation regulating human cloning. Part IV discusses the future of legislation in the United States as well as a number of factors which need to be addressed to draft comprehensive legislation.